Hygien, städning och desinfektion inom smådjurssjukvården - Lundqvist, Maria; Löfström, Susanne (SLU/Dept. of Animal Environment and Health (until 231231), 2008)
The aim of this report is to create an easily accessible guide to basic hygiene, cleaning and disinfection within the small animal practice. It is based on a literature study, using mainly research from the public health sector, due to the lack of relevant scientific reports within the veterinary field.